2015
DOI: 10.1016/j.scog.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Insight and subjective measures of quality of life in chronic schizophrenia

Abstract: Lack of insight is a well-established phenomenon in schizophrenia, and has been associated with reduced rater-assessed functional performance but increased self-reported well-being in previous studies. The objective of this study was to examine factors that might influence insight (as assessed by the Insight and Treatment Attitudes Questionnaire [ITAQ] or PANSS item G12) and subjective quality-of-life (as assessed by Lehman QoL Interview [LQOLI]), using the large National Institute of Mental Health Clinical An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 60 publications
9
28
1
Order By: Relevance
“…Sui et al 34 examined the link of insight with non-adherence in the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study, a nationwide public health-focused clinical trial of antipsychotic medication, and found that patients with poor insight who were most likely to discontinue treatment also had relatively more severe levels of psychopathology.…”
Section: Insight and Treatment Engagementmentioning
confidence: 99%
“…Sui et al 34 examined the link of insight with non-adherence in the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study, a nationwide public health-focused clinical trial of antipsychotic medication, and found that patients with poor insight who were most likely to discontinue treatment also had relatively more severe levels of psychopathology.…”
Section: Insight and Treatment Engagementmentioning
confidence: 99%
“…The large-scale CATIE study showed that correlation between PANSS item G12 and insight as assessed by Insight and Treatment Attitudes Questionnaire (ITAQ) total score was 0.49: [30];(p<0.001, N=1099) and that the PANSS G12 had a number of functional correlates in that sample. In these analyses, impairment was defined as a score of 4 or greater on PANSS item 12.…”
Section: Lurasidone Dose and Cognitive Effectsmentioning
confidence: 96%
“…Treatmentrelated improvement in insight from baseline to the 6-month endpoint was significantly correlated with better scores for measures of neurocognitive performance (p<0.05), functional capacity (p<0.05) and quality of well-being (p<0.05) across treatment groups and study periods. Poor insight contributing to deficits in illness awareness and objective measures of cognitive and functional performance is prevalent in schizophrenia [30,[32][33][34][35]. Lack of insight was associated with inability to complete neurocognitive testing and provide valid scores at baseline visit in acute study phase.…”
Section: Longitudinal Analysis Of Outcomesmentioning
confidence: 99%
See 2 more Smart Citations